Изучение активности синтеза генетического материала в клетке гетерозисных гибридов томата и хлопчатника - Мамедова, А.Д.; Алиев, Р.Т. (Фактори експериментальної еволюції організмів, 2014)
Aims. The study of changes in the content of nucleic acids in the cell of heterotic plants in comparison with parental forms. Methods. Mitochondria and chloroplasts were isolated by the differential centrifugation. Nucleic acids content in were determined by the method described in the works of V.G. Konareva and S.L. Tyutereva (1970). Results. DNA content per one cell in leaf’s tissue in all hybrid combinations of cotton was higher than in parental varieties. The number of cells per unit of square of leaf surface was lesser, while the size of one cell was larger. In heterotic hybrids both mitochondrions and chloroplasts may contribute to increasing of cell energy-supply. Conclusions. One can suppose that in case of increased load on nuclear, mitochondrial and chloroplast genetic system of plant cell, the hybrid, which has raised energy-supply for biosynthesis of plastic matter, develops the high heterosis effect.

Key words: heterosis, RNA, DNA, cell, mitochondria, chloroplasts.